- “THE RELATIONSHIP OF MOTHER'S PARENTING PATTERNS IN FEEDING WITH THE INCIDENT OF STUNTING IN TODDLER AGE 24 MONTHS - 60 MONTHS”: “THE RELATIONSHIP OF MOTHER'S PARENTING PATTERNS IN FEEDING WITH THE INCIDENT OF STUNTING IN TODDLER AGE 24 MONTHS - 60 MONTHS” - novia, siska (LPPM Universitas dr. Soebandi, 2024)
Abstract The problem phenomenon that exists among mothers of toddlers in Panduman Village, Jelbuk sub-district is that many mothers are found who do not really pay attention to how they feed their children, they tend to give their children simple food without paying attention to the nutritional value of the food. The aim of this community service is to identify maternal parenting patterns in feeding toddlers, identify stunting incidents in toddlers, and analyze the relationship between maternal parenting patterns in feeding toddlers and stunting incidents in toddlers. This activity is carried out by providing counseling using a questionnaire sheet to mothers who have stunted toddlers and measuring their height with a microtoise. Mothers who have stunted toddlers are very enthusiastic and active in receiving materials and taking part in activities to understand how to feed toddlers properly and correctly. Keywords: toddlers, mother's parenting style, stunting Abstrak Fenomena masalah yang ada pada ibu balita di Desa panduman kecamatan jelbuk yaitu banyak dijumpai ibu yang tidak terlalu memperhatikan cara memberikan makan pada anaknya, mereka cenderung memberikan makanan pada anaknya secara sederhana tanpa memperhatikan nilai gizi pada makanan. Tujuan pengabdian Masyarakat ini untuk Mengidentifikasi pola asuh ibu dalam pemberian makan pada balita, Mengidentifikasi kejadian stunting pada balita, dan Menganalisis hubungan pola asuh ibu dalam pemberian makan dengan kejadian stunting pada balita. Kegiatan ini dilakukan dengan memberikan penyuluhan menggunakan lembar kuesioner pada ibu yang memiliki balita stunting dan melakukan pengukuran tinggi badan dengan microtoise. Ibu yang memiliki balita stunting sangat antusias dan aktif dalam menerima materi dan mengikuti kegiatan untuk memahami cara pemberian makan terhadap balita dengan baik dan benar. Kata kunci : balita, pola asuh ibu, stunting